Perinatal innovations for calves and piglets - Mazzardo Bortoluzzi, Eduarda (Kansas State University, 2022)
In animal production, the ultimate goal is to fulfill the pillars of sustainability to ensure that future generations will have access to natural resources and animal sources to meet their needs. The perinatal period offers many challenges for both dams and their offspring regardless of species. Alternatives and refined methods are needed to improve animal efficiency, care, and welfare. For this dissertation two high impact animal production systems were evaluated for perinatal methods: cow-calf and nursery swine. Twinning is a controversial topic among producers because even though the possibility of increasing weaned kg/cow seems promising, birth difficulties and perinatal mortality can threaten the achievement of this goal. To achieve twinning in an Angus-cross herd, a Fixed-Time Artificial Insemination (FTAI) protocol was used. Cows were inseminated with black Angus semen and 7 d (n = 75) after insemination an embryo transfer was performed to the contralateral uterine horn containing the corpus luteum (n=63). Cows that were inseminated and received an embryo achieved a pregnancy risk of 61.9%, with 42.9% carrying twins and 19% carrying singletons. Second born twins required some assistance during parturition. Survival proportions were not different among twins and singletons (81.6% and 80%, respectively; P > 0.1). Raising methods for twins and singletons were also discussed. When twins were born as twins, but one got grafted to another cow, they underperformed compared to singletons and twins raised both with their dam. The usage of the proposed twinning protocol successfully produced twins on commercial Angus herds. This is an opportunity for producers to increase the amount of weight weaned by cow (kg/cow) and improve sustainability. However, this protocol works better on a small herd or a subset herd that will be closely monitored for appropriate intake and parturition. Colostrum supplementation can be an important management tool when calving heifers and twins. Concern is raised due to lower concentration of immunoglobulins and small volumes of first-calf heifers’ colostrum. A randomized field trial was conducted to compare the supplementation of a commercial colostrum product (CS) and a control treatment (control). Immune measures, neonatal behaviors, and growth were assessed for both treatments. No significant differences in IgG concentrations or growth measures were found between treatments (P > 0.1). Latency of first nurse was found to be higher for calves on CS treatment (P > 0.05). Even though, immune measures and growth were not affected by colostrum supplementation, a delay was seen in nursing behaviors. This does not dismiss the usage of colostrum replacement products in challenging situations, such as cold stress and no colostrum available from dam. Precision livestock tools have been developed to assist management of animals. These tools are important especially during the neonatal periods to identify individual animals facing subclinical sickness that are not obvious to human observations. The nursery phase for piglets is very challenging due to many stressors (e.g., ear notching, ear tagging, tail docking, teeth clipping, and castration of males) that can implicate their naïve immune system. A study was conducted to use a precision livestock tool (NUtrack) to assess behavior of piglets either LPS-challenged (challenged) or non-challenged (saline injection; sham) and compare to human observations. The LPS challenge induced transient sickness in piglets. Receiver operating characteristics (ROC) curve and area under the curve (AUC) were used to analyze the data from human observation scores and NUtrack. Human observation presented a sensitivity of 88.5% and a specificity of 85% with an AUC of 0.871. While NUtrack evaluated pivot behaviors, presented a sensitivity of 96.8% and a specificity of 92.7% with an AUC of 0.999 in the day of the challenge. The sensitivity and specificity of human observations declined AUC < 0.6 within 2 d after challenge. NUtrack presented a good ability to identify challenged pigs and can aid caretakers to identify subtle behavior modifications. Innovations for perinatal period in cattle and swine are indispensable to maintain the sustainability of animal productions. The management tools and protocols discussed aim to improve efficiency and animal welfare. Twining can be used to face sustainable challenges producers face in cow-calf operations, colostrum management is important to support passive immune transfer, and precision livestock technology can aid labor workers during management decision-making.
Keywords: Twinning; Colostrum; Precision animal technology; Sustainability; Calf; Piglet